2020
DOI: 10.3390/pharmaceutics12020153
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum-Associated Degradation-Dependent Processing in Cross-Presentation and Its Potential for Dendritic Cell Vaccinations: A Review

Abstract: While the success of dendritic cell (DC) vaccination largely depends on cross-presentation (CP) efficiency, the precise molecular mechanism of CP is not yet characterized. Recent research revealed that endoplasmic reticulum (ER)-associated degradation (ERAD), which was first identified as part of the protein quality control system in the ER, plays a pivotal role in the processing of extracellular proteins in CP. The discovery of ERAD-dependent processing strongly suggests that the properties of extracellular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 192 publications
0
5
0
Order By: Relevance
“…14 Similarly, overexpression of a dominant-negative ubiquitin mutant lacking all of the lysine residues in mammalian cells abrogates polyubiquitination and potently inhibits MHC I-restricted processing of endoplasmic reticulum (ER)-targeted proteins. 15 Accumulating evidence suggests that MHC I-restricted processing of exogenous proteins for cross-presentation involves ER-associated degradation (ERAD), [16][17][18][19] a mechanism mediating retrotranslocation of misfolded proteins from the ER back to the cytoplasm for proteasomal degradation. 20 ERAD also mediates processing of extracellular proteins involved in antigen cross-presentation.…”
Section: Antigen Processing and Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Similarly, overexpression of a dominant-negative ubiquitin mutant lacking all of the lysine residues in mammalian cells abrogates polyubiquitination and potently inhibits MHC I-restricted processing of endoplasmic reticulum (ER)-targeted proteins. 15 Accumulating evidence suggests that MHC I-restricted processing of exogenous proteins for cross-presentation involves ER-associated degradation (ERAD), [16][17][18][19] a mechanism mediating retrotranslocation of misfolded proteins from the ER back to the cytoplasm for proteasomal degradation. 20 ERAD also mediates processing of extracellular proteins involved in antigen cross-presentation.…”
Section: Antigen Processing and Presentationmentioning
confidence: 99%
“…20 ERAD also mediates processing of extracellular proteins involved in antigen cross-presentation. 19 Thus, approaches to enhance ER entry of protein antigens, such as Grp170 chaperone-based vaccine adjuvant system, improve the efficiency of cross-presentation and induction of CD8 T cell responses in cancer immunotherapy. 19,21 Ubiquitination has a vital role in ERAD-dependent protein processing.…”
Section: Antigen Processing and Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 Then, the ERAD pathway was activated and involved in misfolded protein degradation to alleviate ER stress. 18 Previous study demonstrated that RT alone was capable of inducing mild ER stress. 19 Enhanced and prolonged ER stress was able to amplify ICD-associated immunogenicity in cancer; in contrast, weak or mild ER stress could be mitigated by the activation of ERAD pathway and had limited efficacy in triggering ICD.…”
Section: Introductionmentioning
confidence: 99%
“… 19 Enhanced and prolonged ER stress was able to amplify ICD-associated immunogenicity in cancer; in contrast, weak or mild ER stress could be mitigated by the activation of ERAD pathway and had limited efficacy in triggering ICD. 18 , 20 Thereby, targeting ERAD pathway may enhance radiation-induced ER stress and improve the immunogenicity of tumor cells. In recent years, several chemotherapeutic agents have been depicted to trigger ICD in various tumor models; however, the commonly used cytotoxic drugs in EC including fluorouracil and cisplatin were inefficient to induce ICD.…”
Section: Introductionmentioning
confidence: 99%